2018
DOI: 10.1016/j.apcatb.2018.03.091
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient Ni/CeO2-Al2O3 catalysts for CO2 upgrading via reverse water-gas shift: Effect of selected transition metal promoters

Abstract: In the context of Carbon Capture and Utilisation (CCU), the catalytic reduction of CO 2 to CO via reverse watergas shift (RWGS) reaction is a desirable route for CO 2 valorisation. Herein, we have developed highly effective Ni-based catalysts for this reaction. Our study reveals that CeO 2 -Al 2 O 3 is an excellent support for this process helping to achieve high degrees of CO 2 conversions. Interestingly, FeO x and CrO x , which are well-known active components for the forward shift reaction, have opposite ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(89 citation statements)
references
References 44 publications
3
86
0
Order By: Relevance
“…When reforming is envisaged as a downstream tar upgrading unit after gasification, the most interesting temperature interval for atmospheric reforming is between 600 and 900 • C, since the gasification effluent temperature will normally be lower than 900 • C [33]. Research also suggested that high temperature might reduce H 2 yield as the reverse water-gas shift reaction is favoured due to its endothermic nature [34][35][36]. The experiments were conducted at different temperatures to investigate the most suitable conditions for toluene conversion and H 2 production.…”
Section: Influence Of Temperature On Toluene Steam Reformingmentioning
confidence: 99%
“…When reforming is envisaged as a downstream tar upgrading unit after gasification, the most interesting temperature interval for atmospheric reforming is between 600 and 900 • C, since the gasification effluent temperature will normally be lower than 900 • C [33]. Research also suggested that high temperature might reduce H 2 yield as the reverse water-gas shift reaction is favoured due to its endothermic nature [34][35][36]. The experiments were conducted at different temperatures to investigate the most suitable conditions for toluene conversion and H 2 production.…”
Section: Influence Of Temperature On Toluene Steam Reformingmentioning
confidence: 99%
“…Regardless of the hydrogen inlet concentration, CO2 conversion approached the respective equilibrium values within ~5% at around 380 °C. Several catalytic systems employed for rWGS have been reported to function under thermodynamic limitation at the medium-high or high temperature regime [103][104][105]. As for the selectivity to CH4, it increased slightly, from about 1.0% for a H2:CO2 ratio of 1:1 to 5.1% for a ratio of 9:1.…”
Section: Effect Of H 2 :Co 2 Ratiomentioning
confidence: 99%
“…Ru [27], Cu [28][29][30], Fe [31,32], and Ni [33,34] have been utilized. Various supports such as CeO 2 [28,35,36] , SiO 2 [37,38] , Al 2 O 3 [39,40] , ZrO 2 [29] , TiO 2 [25,41] , zeolite [13] have been used.…”
Section: Co 2 + Hmentioning
confidence: 99%